THERMAL ANALYSIS AND APPLICATION OF ROLL BOND SOLAR ABSORBERS FOR HEATING AND COOLING IN RESIDENTIAL BUILDINGS - Avsec, Jurij; Brandl, Daniel; Schober, Helmut; Novosel, Urška; Ferčec, Janko (Journal of Energy Technology, 2024)
The use of renewable energy sources will have to be increased significantly over the coming decades. The potential of solar energy in Slovenia represents the largest share of renewable energy sources. This article shows the use of roll bond solar absorbers for the heating and cooling of houses. For this purpose, we performed a numerical simulation of solar absorbers and theoretical calculations.